2020
DOI: 10.2147/cmar.s242615
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Regulatory Role of circRNA_101308 in Cervical Cancer and the Prediction of Its Mechanism</p>

Abstract: Purpose: Accumulating evidence indicates that circular RNAs (circRNAs) are closely involved in canceration and cancer progression. However, the role of circRNAs in cervical cancer (CC) is largely unknown. Here, we characterized the role of circRNA_101308 in CC. Materials and Methods: The expression of circRNA_101308 in CC tissues was measured by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Then, circRNA_101308 was overexpressed in CC cells to detect its function by proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…miR-196a-5p and miR-196a-3p are two , and we also previously reported that it was associated with occurrence of cancers [10]. As a regulator, it could be also regulated by non-coding RNAs, such as lncRNA FEZF-AS1 [11], circRNA 101308 [12], H19 [13], lncRNA SNHG1 [14], which were involved in tumorgenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…miR-196a-5p and miR-196a-3p are two , and we also previously reported that it was associated with occurrence of cancers [10]. As a regulator, it could be also regulated by non-coding RNAs, such as lncRNA FEZF-AS1 [11], circRNA 101308 [12], H19 [13], lncRNA SNHG1 [14], which were involved in tumorgenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 89%
“…Meanwhile, polymorphism in miR-196a-2 was reported to confer occurrence risk or progression of cancers, such as it was associated with HCC recurrence after liver transplantation [ 9 ], and we also previously reported that it was associated with occurrence of cancers [ 10 ]. As a regulator, it could be also regulated by non-coding RNAs, such as lncRNA FEZF-AS1 [ 11 ], circRNA 101308 [ 12 ], H19 [ 13 ], lncRNA SNHG1 [ 14 ], which were involved in tumorigenesis and tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Another circRNA, circ_0005576, has been associated with a higher pathological stage and lymph node metastasis (50). However, alternative studies have indicated that reduced circRNA expression also promotes metastasis; Jiao et al (51) revealed that low expression levels of circRNA_101308 were associated with deep myometrial invasion and lymph node metastasis. Therefore, selecting the appropriate circRNA biomarker for a specific pathology requires more thorough consideration.…”
Section: Iii) Circrnas As Biomarkers Of Cervical Cancer Metastasismentioning
confidence: 99%
“…CircRNA_101308 expression was also revealed to be decreased in cervical cancer tissues and cell lines, compared with that in normal tissues. CircRNA_101308 can bind various different miRNAs and regulate their downstream genes to suppress the proliferation, invasiveness and metastasis of cervical cancer cells, both in vitro and in vivo (51). Furthermore, circ-ITCH has been revealed to be associated with the regulation of tumor growth, and the proliferation and apoptosis of cancer cells in bladder (59) and breast cancer (60).…”
Section: Iii) Circrnas As Biomarkers Of Cervical Cancer Metastasismentioning
confidence: 99%
“…The studies in this paper interrogate the utility of MVC in preclinical GBM models. MVC and other CCL5-CCR5 pathway inhibitors are also undergoing clinical evaluation for multiple tumor types 6 . The CCL5-CCR5 signaling axis has been studied extensively and contributes to tumor progression both by direct effects on proliferation and by indirect induction of angiogenesis and recruitment of immune cells to the GBM microenvironment 7,8 .…”
mentioning
confidence: 99%